2007
DOI: 10.1042/bst0351175
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine metabolism in diabetes

Abstract: An increase in the plasma level of Hcy (homocysteine), an intermediate in the catabolism of methionine, has been identified as a risk factor for many diseases including CVD (cardiovascular disease). CVD is the major cause of death in patients with diabetes mellitus. Therefore the study of Hcy metabolism in diabetes mellitus has been a major focus of current research. Studies conducted in our laboratory were able to show that in both Type 1 and Type 2 diabetes with no renal complications, the plasma Hcy levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
64
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(71 citation statements)
references
References 44 publications
5
64
0
2
Order By: Relevance
“…Our major findings show that the contents of LPO, Hcy and NO 3 -have increased significantly in the heart of diabetic rats. These results are in agreement with other findings [20][21][22]. As we know, vit E is one of the fat-soluble vitamins and is considered as an important antioxidant.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our major findings show that the contents of LPO, Hcy and NO 3 -have increased significantly in the heart of diabetic rats. These results are in agreement with other findings [20][21][22]. As we know, vit E is one of the fat-soluble vitamins and is considered as an important antioxidant.…”
Section: Discussionsupporting
confidence: 83%
“…The reasons for increasing the Hcy amount are the changes that occurred in the enzymes during Hcy metabolism, and an increase of Hcy in the blood [22]. Also, this affects the main Hcy catabolism organs such as kidney and liver, changes their function, and decreases Hcy catabolism, leading to excretion of Hcy and an increase in the amount of Hcy in the blood [30].…”
Section: Discussionmentioning
confidence: 99%
“…These data demonstrate another potential source of the formaldehyde in diabetes that warrants evaluation, and suggest a possible metabolic adaptation that has been unrecognized in the literature. There are studies that have demonstrated upregulation of elements of the methionine cycle (52,66), but these studies were unable to evaluate the entire pathway concurrently and that is a particular strength of the present data.…”
Section: Ajp-endocrinol Metabmentioning
confidence: 60%
“…Existen dos vías independientes de remetilación de la Hcy: la primera catalizada por la enzima metionina sintetasa (MS) y la segunda por la betaína: homocisteína metiltransferasa (BHMT); ambas conducen a la formación de metionina. Por otro lado, la Hcy puede ser irreversiblemente convertida en cisteína, mediante la vía de transulfuración, reacción catalizada por las enzimas cistationina-β-sintasa (CBS) y cisteína-γ-liasa (CGL) 25,26 . El metabolismo de la Hcy-Metionina se encuentra alterado en la DM1, ya que los niveles de insulina son capaces de modular la actividad de las enzimas participantes en el ciclo.…”
Section: Discussionunclassified